Completion of Multi-Criteria Decision Making Using the Weighted Product Method on the Server Maintenance Vendor Selection System - Rini Nuraini; Dedy Alamsyah; Ri Sabti Septarini; Alfry Aristo J Sinlae (Institute of Computer Science (IOCS), 2022)
For companies that use information systems or websites in their business activities, server maintenance is an important thing. For this reason, the selection of a server maintenance vendor is crucial. Vendor determination usually begins with gathering information and holding a leadership meeting based on the assumptions of the decision maker. But this method is time consuming and less objective. Vendor selection is a multi-criteria problem where each criterion has a different importance. This can be solved by using the Multi-Criteria Decision Making (MCDM) approach. Weighthet Product (WP) is one of the methods of solving MCDM. The purpose of this research is to develop a decision support system to determine the best maintenance vendor using the Weighted Product (WP) method. The system is built using a waterfall system development approach that starts from analysis, design, coding and testing. The developed system has the ability to manage alternatives, criteria, alternative assessments, calculations with WP, and displays the best alternative results with WP. From the results of black-box testing, it shows that the developed system can function and run well. In addition, the results of manual calculations with the system show the same results.